2016
DOI: 10.1002/dvg.22949
|View full text |Cite
|
Sign up to set email alerts
|

Cre‐dependent DREADD (Designer Receptors Exclusively Activated by Designer Drugs) mice

Abstract: DREADDs, designer receptors exclusively activated by designer drugs, are engineered G protein-coupled receptors (GPCR) which can precisely control GPCR signaling pathways (for example, Gq, Gs and Gi). This chemogenetic technology for control of GPCR signaling has been successfully applied in a variety of in vivo studies, including in mice, to remotely control GPCR signaling, for example, in neurons, glia cells, pancreatic beta-cells, or cancer cells. In order to fully explore the in vivo applications of the DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(187 citation statements)
references
References 20 publications
2
185
0
Order By: Relevance
“…We took advantage of an inhibitory DREADD in which a modified human muscarinic M4 receptor is coupled to Gi (hM4Di). We employed a newly developed R26R-LSL-hM4Di/mCitrine mouse line that expresses floxed hM4Di and mCitrine from the R26 locus 61 (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We took advantage of an inhibitory DREADD in which a modified human muscarinic M4 receptor is coupled to Gi (hM4Di). We employed a newly developed R26R-LSL-hM4Di/mCitrine mouse line that expresses floxed hM4Di and mCitrine from the R26 locus 61 (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Ablation of TRPV1-lineage neurons eliminates heat- and cold responses but mechanical sensitivity is not affected, which shows TRPV1-lineage neurons do not include mechano-sensitive neurons 40 . Second, we used a mouse line conditionally expressing an engineered human muscarinic 4 receptor (hM4Di; Gi-coupled Designer Receptors Exclusively Activated by Designer Drugs (DREADD)) from Rosa26 locus (R26-LSL-hM4Di; https://www.jax.org/strain/026219) 61 . Upon removal of loxP-stop-loxP cassette (LSL) by Cre recombination, the Gi-coupled hM4Di is expressed and the neuronal function is silenced by the administration of clozapine-N-oxide (CNO).…”
Section: Methodsmentioning
confidence: 99%
“…Because silencing mWAKE DMH neurons led to a mild phenotype, we chose to inhibit the broad mWAKE + network. To do this, we crossed transgenic mice expressing Cre-dependent DREADD-hM4Di (LSL-Gi) 22 to mWAKE (Cre/+) mice to generate mWAKE (Cre/+) ; LSL-Gi progeny. We first examined the expression pattern of the DREADD-hM4Di in these mice by immunostaining and found that it largely recapitulated the original expression pattern of the mWAKE (Cre/+) mice (Extended Data Fig.…”
Section: The Mwake + Network Intersects With Multiple Arousal-relatedmentioning
confidence: 99%
“…Urban et al () demonstrated that acute or chronic selective activation of hM3Dq‐expressing dorsal raphe nucleus serotonergic neurons with CNO resulted in distinct metabolic brain responses and behaviours. Moreover, using DREAMM and slice electrophysiology, they observed that hM3Dq exhibited robust and continuous activity after long‐term (3 weeks) stimulation with CNO (Urban, Zhu et al, ). Most recently, Bonaventura et al () demonstrated with DREAMM that JHU37160‐mediated activation of hM3Dq‐ or hM4Di‐expressing dopaminergic D 1 neurons resulted in decreased or increased metabolism in distinct, largely non‐overlapping brain networks, respectively (Bonaventura et al, ).…”
Section: Dreadds Combined With Imaging Techniquesmentioning
confidence: 99%
“…In vivo, DREADDs expression in specific cell types is typically achieved by using transgenic mouse models or focal viral vector injections targeting selected brain areas. Various transgenic mouse models have been developed to specifically express DREADDs in selected cell populations by using specific promoters (Farrell et al, ; Guettier et al, ), the transcriptional Tet‐On/Off system (Alexander et al, ) or the Cre‐recombinase system (Zhu et al, ). Transgenic lines lower the inter‐animal variability by offering similar expression levels of DREADDs across all animals, while losing the ability to non‐invasively manipulate the receptors in a region‐specific manner.…”
Section: Introductionmentioning
confidence: 99%